Woodland expansion and upland management strategy dilemmas for biodiversity and carbon storage in the Cairngorms national park - Valette, Michel; Newey, Scott; Schreckenberg, Kate; Dawson, Terence P. (Frontiers in Environmental Science, 2024)
Nature-based solutions are increasingly advocated to mitigate climate change and biodiversity crisesloss, while improving ecosystem resilience and providing additional ecosystem services. In Scotland, woodland expansion and restoration of degraded peatlands are expected to play a major role in meeting net-zero emissions by 2045 and have prompted debates about the impact of increased woodland cover and prescribed firesfire on the biodiversity and ecosystem services provided by upland landscapes. In alignment with national policy, the Cairngorms National Park, the UK's largest national park, has committed to an ambitious programme of woodland expansion and peatland restoration in a landscape dominated by heather moorlands that is predominantly managed through prescribed burning for game management. Using the Native Woodland Model and the InVest modelling platform, we assessed the effects of five land cover and land use change scenarios, with different levels of prescribed fire regulation and woodland expansion, to evaluate their benefits and costs on biodiversity and carbon sequestration. Results show that changing the extent and management of habitats will result in different carbon sequestration pathways, as well as biodiversity winners and losers. The scenario presenting greater benefits for the conservation of biodiversity also has lower above-ground carbon sequestration potential and a larger negative impact on red grouse habitats, thus being less profitable to sporting estates. Hence, trade-offs will be necessary to achieve optimal carbon sequestration and biodiversity gains, with a potential role played by the continuation of prescribed fires and traditional moorland management practices as well as complementary grants and support measures based on biodiversity benefits rather than carbon sequestration. The results from this study could support discussions regarding future management of the uplands, trade-offs between loss of carbon in soils, carbon